The Role of Language in the Formation and Development of Society - Ahmad, Quraishi Nesar (International journal of multicultural and multireligious understanding, 2025)
The article talks about the importance of language in the formation and development of society and the problem of the disappearance of entire languages. The emergence of language and speech leads a person not only to understanding in communicating with each other, but also develops art and religion. Thanks to language, such forms as singing, spells, and incantations appeared, which developed musical and ritual culture. Initially, people believed in the word as a real action, with the help of which it was possible to drive away disasters and evil forces, to call for the good of one's tribe. With the help of religious worldview, man tried to know and understand the world around him. The more a person reflects and expresses his reflections in linguistic form, the more society itself develops.